1987
DOI: 10.2307/145744
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination, Human Capital, and Black-White Unemployment: Evidence from Cities

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press and The Board of Regents of the University of WisconsinSystem are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
(4 reference statements)
0
19
0
Order By: Relevance
“…Larger residuals, however, would also be 6 The fundamental idea that discrimination is associated with a willingness to bear a cost for this taste is due to Becker (1957). See also Schulman (1986) for an adaptation of these concepts to a business cycle context. consistent with other unobserved factors such as tenure and educational quality being more important determinants of employment during recessions.…”
Section: The Last Hired First Fired Hypothesismentioning
confidence: 99%
“…Larger residuals, however, would also be 6 The fundamental idea that discrimination is associated with a willingness to bear a cost for this taste is due to Becker (1957). See also Schulman (1986) for an adaptation of these concepts to a business cycle context. consistent with other unobserved factors such as tenure and educational quality being more important determinants of employment during recessions.…”
Section: The Last Hired First Fired Hypothesismentioning
confidence: 99%
“…3 Discrimination in hiring against women (and minorities) is more likely to decline if the labor market is tight enough (i.e., there is full employment), so that women (and minorities) can move up the hiring queue and discriminatory employers can thus be penalized, and not when there is substantial unemployment in the labor market (Shulman 1987). …”
Section: International Trade Wages and Employmentmentioning
confidence: 99%
“…With two exceptions, however, studies of wage discrimination against blacks have ignored the wage-employment relationship, implicitly assuming that labor supply schedules are perfectly inelastic (Cain 1986). Shulman (1987) used complaints to the EEOC as a proxy for the incidence of employer discrimination, and found that discrimination reduced the probability of employment for black workers. The findings were not, however, linked to estimates of wage discrimination.…”
mentioning
confidence: 99%